Synthesis and Photophysical Properties of Triazolyl Ir III Nucleosides - Passays, Johan; Rubay, Christophe; Marcélis, Lionel; Elias, Benjamin (European journal of inorganic chemistry, 2017)
DNA‐based nanomaterials are the subject of numerous researches. A series of modified nucleobases were synthesized either to construct a double helix where the natural H‐bonded bases are replaced by metal‐coordinated liganosides or to introduce a punctual modification inside a natural DNA structure. Thanks to their photophysical and photochemical properties, iridium(III) complexes are of increasing interest in the development of sensors and photoreactants for biochemical applications. In this view, we previously demonstrated that some Ir III complexes are able to photoreact with DNA through photoinduced electron transfer. In this study, we report the synthesis and characterization of nucleosides bearing iridium complexes with unaltered properties compared to their parent complexes.